Smart City: desenvolvimento sustentável, sociedade de controle e cidade inteligente - Gaudencio, João Rafael da Cruz (2015)
This Master's Dissertation reflects upon the subject Smart City: sustainable development, control society and the city of the future. In this thematic framework, the object of study is the contemporary scenario of Smart City development. Founded upon theoretical and empirical elements that are assumptions about the aforementioned object, the research proposes a line of argument guided by sociological and technological concepts. In the outline, the concepts of sustainability and technology pertain to proposed actions and mobilization for social engagement and for the political agenda, promoting equitable development. However, some obstacles to contextualizing the Smart City are, for example, the control society, and particularly, regulatory policies. Thus, an ideal society is established based on media visibility about private initiatives promoted by corporations for the equitable advancement of people. Leading the community in a meaningful way presupposes essential interests that raise the social level in the world in the search for a green economy. The counterpart of sustainability is the result of rapacious industrialization, which seeks to satisfy social expectations and, through the media, interferes in the customs and desires in popular culture. Based on these theoretical and practical elements, the research problem consists in the growing human and social evolutionary complexity which points to possible new civil turmoil. This problem concerns the question of how Smart Cities are currently structured and their future development. This research involved the use of combined methods of qualitative and hands-on analysis to discover the directions the Smart City proposes for society and for consumption. The analysis of the corpus of research delves into the current methods of customs as they pertain to interaction with the ecosystem and with man engaged in conscious sustainable development. In addition, the methodological procedures involved a literature review. The thematic link between sustainability, technology, control society and consumption was based on the epistemological framework of theories of communication, knowledge, administration and marketing, sustainability and consumption. Authors that stand out in this study are Foucault, Deleuze, Parkin and Kotler. With these characteristics, the relevance of this research centers on deepening the debate in the discursive field of politics, the social, the current context and sustainable consumption